1992
DOI: 10.1007/bf00402551
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between plasma testosterone and plasma insulin in healthy adult men: the Telecom Study

Abstract: Plasma insulin is a risk factor for diabetes mellitus and cardiovascular disease in men. We investigated the association between plasma testosterone and plasma insulin in an occupational sample of 1292 healthy adult men. Total plasma testosterone decreased with each decade of age and insulin increased with each decade of age. In these cross-sectional data, this significant graded inverse association between testosterone and insulin was independent of age. The association was reduced but not explained by the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
4

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 46 publications
3
77
1
4
Order By: Relevance
“…RRs were altered considerably for the two extreme sleep groups when adjusted for testosterone, which is inversely related to waist circumference. In previous studies, low levels of testosterone have been associated with risk factors for diabetes including obesity (21), body fat distribution (increased waist-to-hip ratio) (22), and elevated levels of insulin and glucose (22,23). Low levels of testosterone were previously related to diabetes in this cohort (24) and others (25).…”
Section: Biological Mechanismsmentioning
confidence: 53%
“…RRs were altered considerably for the two extreme sleep groups when adjusted for testosterone, which is inversely related to waist circumference. In previous studies, low levels of testosterone have been associated with risk factors for diabetes including obesity (21), body fat distribution (increased waist-to-hip ratio) (22), and elevated levels of insulin and glucose (22,23). Low levels of testosterone were previously related to diabetes in this cohort (24) and others (25).…”
Section: Biological Mechanismsmentioning
confidence: 53%
“…34,227,228 There is positive correlation between serum testosterone levels and insulin sensitivity in men across the full spectrum of glucose tolerance 229 and an improvement of insulin sensitivity was noted after replacement. 230 Although Abate et al 231 found no association between low plasma levels of bioavailable testosterone and insulin resistance in eugonadal men; a recent larger study (NHANES [National Health and Nutrition Examination Survey]) showed that low free and bioavailable testosterone levels, even in the normal range, are associated with diabetes, independent of adiposity.…”
Section: 224mentioning
confidence: 99%
“…Cross-sectional studies demonstrate an inverse relationship between testosterone and fasting insulin levels in men independent of age, obesity, and body fat distribution (7)(8)(9)(10)(11). A link between testosterone deficiency and diabetes has also been suggested with the demonstration that men with type 2 diabetes have lower testosterone levels than weight-matched nondiabetic control subjects (12,13).…”
mentioning
confidence: 99%